Emergency Cardiac Surgery in Patients on Direct Oral Anticoagulants - De Paulis, Stefano; Bruno, Piergiorgio; Massetti, Massimo (Frontiers in Cardiovascular Medicine, 2022)
Cardiac surgery carries a high risk of perioperative bleeding and emergency surgery is one of the most significant factors in the determination of this risk. When perioperative bleeding ensues, blood products administration and surgical re-exploration are generally required, with concomitant increase in perioperative morbidity and mortality (1). Bleeding risk is amplified in patients on anticoagulants and the expanding indication for direct oral anticoagulants (DOACs) has confronted perioperative physicians with new challenges related to the peculiar pharmacology of these agents. Guidelines for the management of bleeding patients taking DOACs exist but many uncertainties remain for their application to the cardiac surgery setting.